English Student’s Teaching Skills Applied in Microteaching Class Muhammadiyah University of Bengkulu - Fetriani Fetriani; Emi Fitri Lolita; Eki Saputra (Universitas Muhammadiyah Enrekang, 2021)
The objective of this research was to investigate and describe the English students’ teaching skills applied in Microteaching Class at University of Muhammadiyah Bengkulu Academic year 2020/2021. The design of this research was a descriptive qualitative research. This research took the subject of the study with total 25 students at the sixth semester that enrolled microteaching class at English program. The researcher used observation checklist to obtain the data. The findings of this research revealed that the teaching skills applied by English students in Microteaching Class are questioning skills, reinforcement skills, variation skill, explaining skills, opening skill, small group discussion skill, classroom management skills, organizing small group work and individual work, closing skill; and using teaching media skill.